Impacts of the digital economy on urban low-carbon sustainable development - Song, Yaqing; Sun, Xin; Cai, Xiaowei; Liu, Xi (Frontiers in Energy Research, 2024)
As a novel economic form, the digital economy plays an important role in promoting urban low-carbon sustainable development (LCSD). Based on panel data from 270 cities in China from 2011 to 2021, this study used principal component analysis and the global entropy weight method to calculate the level of digital economy development and LCSD as well as to empirically discuss any correlated effects and mechanisms. The research showed that the digital economy has significantly promoted urban LCSD and has become an important source for promoting green low-carbon development. The digital economy can indirectly promote LCSD by accelerating industrial structure upgrading and promoting technological innovation; Moreover, this promotion can show significant threshold characteristics with these factors. When industrial structure upgrading and technological innovation reach a certain threshold, the digital economy can further enhance urban LCSD. The promotion of the digital economy is positively influenced by marketization level and environmental regulation, and it exhibits distinct regional characteristics. During the critical period of economic development and transformation, the government must continuously promote the development of the digital economy, fully release its dividends on LCSD, and implement a differentiated digital development strategy to promote low-carbon economic development according to local conditions.